An antifouling coating, its preparation method and application
By employing a three-layer coating design, combined with piezoelectric sterilization, slow-release antibacterial technology, and super-slippery anti-adhesion technology, the problems of short antifouling cycle, poor environmental performance, and static failure of marine antifouling coatings have been solved, achieving long-lasting, environmentally friendly, and high-performance antifouling effects.
Patent Information
- Application Number
- CN202511612303.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-06
- Publication Date
- 2026-01-30
- Estimated Expiration
- 2045-11-06
AI Technical Summary
Existing antifouling coatings for ships have problems such as short antifouling period, heavy metal pollution, biological resistance and high maintenance costs. Traditional coatings are not effective in preventing fouling in static environments.
It adopts a three-layer coating design, including a bottom layer, an intermediate layer and a top layer. The bottom layer uses piezoelectric fillers to generate a bactericidal effect, the intermediate layer uses Coptis chinensis extract for slow-release antibacterial effect, and the top layer adopts an ultra-smooth biomimetic design, integrating piezoelectric sterilization, chemical antibacterial and physical anti-adhesion functions.
It significantly extends the antifouling cycle of ship hulls to 5-8 years, reduces maintenance costs, meets environmental protection standards, has a low rate of biofouling in static environments, has excellent mechanical performance, and is adaptable to complex marine environments.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of marine engineering technology, specifically relating to an antifouling coating, its preparation method, and its application. Background Technology
[0002] Marine biofouling is a major technical challenge in ship operation, primarily manifested as the attachment and growth of marine organisms such as barnacles, algae, and mussels on the hull surface. This biofouling not only significantly increases the ship's drag, leading to increased fuel consumption, but also accelerates hull corrosion, shortens the ship's service life, and provides a carrier for the cross-regional spread of harmful marine organisms, posing a serious threat to the marine ecological balance. To address this problem, antifouling coating technology for ships has emerged and become an important research direction in the field of marine engineering.
[0003] Traditional antifouling coatings for ships primarily rely on chemical antifouling mechanisms, inhibiting the attachment and growth of marine organisms by adding organotin compounds, cuprous oxide, and other biotoxic substances to the coating. However, existing technologies have significant drawbacks: traditional toxic coatings (containing cuprous oxide) offer good short-term antifouling effects but suffer from heavy metal pollution and biological resistance issues, and their antifouling cycle is only 1-2 years, leading to frequent coating replacements and high maintenance costs. Summary of the Invention
[0004] The purpose of this invention is to provide an antifouling coating, its preparation method, and its application. The antifouling coating provided by this invention, when applied to ship hull antifouling, significantly extends the antifouling cycle of the ship hull, reaching 5-8 years, far exceeding traditional antifouling coatings (1-3 years), reducing the frequency of ship coating replacement and lowering maintenance costs. Simultaneously, the antifouling coating provided by this invention possesses strong surface static antifouling capability, high mechanical strength, and good wear resistance, enabling it to adapt to complex marine environments; furthermore, the preparation method of the antifouling coating is compatible with existing ship production lines.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] This invention provides an anti-fouling coating, comprising a bottom layer, an intermediate layer, and a top layer stacked sequentially;
[0007] The underlying slurry forming the bottom layer comprises the following components by mass fraction: 60-75% epoxy resin, 20-35% piezoelectric filler, 1-5% dispersant, and 0.5-3% defoamer;
[0008] The intermediate layer slurry forming the intermediate layer comprises the following components by mass fraction: 40-50% porous silica, 10-15% Coptis chinensis extract, 30-40% acrylic resin, and 3-5% organic toughening agent;
[0009] The surface slurry forming the surface layer comprises the following components by mass fraction: 80-90% polydimethylsiloxane, 5-10% earthworm mucus mimic, 3-8% crosslinking agent, and 0.5-3% catalyst, wherein the earthworm mucus mimic includes hyaluronic acid and glycerin.
[0010] Preferably, the piezoelectric filler comprises zinc oxide whiskers and / or graphene; the dispersant is BYK-163, and the defoamer is BYK-052.
[0011] Preferably, the porous silica has a pore size of 50~200 nm and a porosity of 50~70%; the Coptis chinensis extract contains ≥90wt% berberine; and the organic toughening agent is dibutyl phthalate.
[0012] Preferably, the mass ratio of hyaluronic acid to glycerol is 1:2 to 2:1; the crosslinking agent is tetraethyl orthosilicate; and the catalyst includes tetrabutyl titanate (TBT) or γ-aminopropyltriethoxysilane (KH-550).
[0013] Preferably, the thickness of the bottom layer is 50-80 μm; the thickness of the intermediate layer is 80-120 μm; and the thickness of the top layer is 5-10 μm.
[0014] This invention provides a method for preparing the antifouling coating described above, comprising the following steps:
[0015] Epoxy resin, piezoelectric filler, dispersant and defoamer are mixed to obtain a base slurry; the base slurry is coated on the substrate surface and then thermo-cured to obtain the base layer;
[0016] Coptis chinensis extract, alcohol solvent, and porous silica are mixed and loaded to obtain a supported carrier; the supported carrier, acrylic resin, and organic toughening agent are mixed to obtain an intermediate layer slurry; the intermediate layer slurry is coated on the surface of the bottom layer and then thermosetting to obtain an intermediate layer on the surface of the bottom layer.
[0017] Polydimethylsiloxane, earthworm slime mimic, crosslinking agent and catalyst are mixed to obtain a surface slurry; the surface slurry is coated on the surface of the intermediate layer and then thermo-cured to obtain a surface layer on the surface of the intermediate layer, thus obtaining the anti-fouling coating.
[0018] Preferably, the method for preparing the porous silica includes the following steps:
[0019] A surfactant solution is obtained by mixing surfactant, potassium chloride, and water.
[0020] The surfactant solution, inorganic acid solution, and silicon source are mixed to obtain a sol solution;
[0021] The sol solution was aged and dried sequentially to obtain a dry gel.
[0022] The dry gel was calcined to obtain the porous silica.
[0023] Preferably, the preparation method of the Coptis chinensis extract includes the following steps:
[0024] The Coptis chinensis herb was extracted with an ethanol-water solution to obtain an extract solution; the extract solution was concentrated to obtain an extract; the extract was dissolved in an acid solution and then purified with a macroporous adsorption resin to obtain an eluent; the eluent was successively concentrated, crystallized and dried to obtain the Coptis chinensis extract.
[0025] Preferably, the substrate is a ship hull; the surface roughness of the substrate is 5~10μm.
[0026] This invention provides the application of the antifouling coating described in the above technical solution or the antifouling coating prepared by the preparation method described in the above technical solution in ship antifouling.
[0027] This invention provides an antifouling coating comprising a bottom layer, an intermediate layer, and a top layer stacked sequentially. The bottom layer slurry forming the bottom layer comprises the following components by mass fraction: 60-75% epoxy resin, 20-35% piezoelectric filler, 1-5% dispersant, and 0.5-3% defoamer. The intermediate layer slurry forming the intermediate layer comprises the following components by mass fraction: 40-50% porous silica, 10-15% Coptis chinensis extract, 30-40% acrylic resin, and 3-5% organic toughening agent. The top layer slurry forming the top layer comprises the following components by mass fraction: 80-90% polydimethylsiloxane (PDMS), 5-10% earthworm mucus mimic, 3-8% crosslinking agent, and 0.5-3% catalyst, wherein the earthworm mucus mimic includes hyaluronic acid and glycerin. The antifouling coating provided by this invention has a piezoelectric catalytic layer as its base layer, which has a piezoelectric bactericidal effect. The mechanism of this piezoelectric bactericidal effect is as follows: During ship navigation or berthing, external forces such as wave impact and water flow disturbance act on the base layer of the antifouling coating, causing mechanical deformation of the piezoelectric filler and generating a piezoelectric effect. This results in the separation of positive and negative charges on the surface of the piezoelectric filler. These positive and negative charges react with seawater and water molecules within microbial cells, respectively, to generate highly oxidizing hydroxyl radicals (·OH) and superoxide anion radicals (O2). -Simultaneously, a localized micro-electric field is formed. Free radicals can disrupt the integrity of microbial cell membranes, leading to leakage of cell contents; the micro-electric field interferes with the metabolic activities and cell division process of microorganisms, ultimately achieving a killing effect on microorganisms. The antifouling coating provided by this invention includes an intermediate layer disposed on the bottom surface. This intermediate layer is an important slow-release layer, and its slow-release mechanism is as follows: Coptis chinensis extract is loaded into the pores of porous silica through physical adsorption (van der Waals forces, electrostatic interactions), and the matrix network formed by acrylic resin encapsulates and constrains the porous silica carrier particles. In a marine environment, seawater slowly penetrates into the interior of the antifouling coating, gradually contacting the Coptis chinensis extract molecules within the pores through diffusion, causing the Coptis chinensis extract to slowly desorb from the carrier pores and permeate through the resin matrix, ultimately achieving controlled release. Berberine, the main active ingredient in Coptis chinensis extract, can act on the cell membrane of microorganisms, disrupting the cell membrane's permeability barrier function and causing leakage of important substances such as potassium ions and nucleotides. Simultaneously, it can inhibit the activity of DNA gyrase and topoisomerase IV within microorganisms, interfering with nucleic acid replication and transcription, thereby inhibiting microbial growth and reproduction, achieving an antibacterial effect. The antifouling coating provided by this invention includes a surface layer disposed on the surface of the intermediate layer. This surface layer is a super-slippery biomimetic layer, which utilizes earthworm mucus mimicry to modify PDMS, significantly reducing bioadhesion while improving its mechanical stability.
[0028] In summary, this invention addresses the problems of existing coatings, such as short antifouling cycles, poor environmental performance, insufficient mechanical properties, and static antifouling failure. The antifouling coating provided achieves comprehensive antifouling protection through a three-layer synergistic structure, combining physical sterilization, chemical antibacterial properties, and physical anti-adhesion. Simultaneously, it ensures the coating's environmental friendliness, high mechanical performance, and industrial applicability, meeting the long-term antifouling needs of various scenarios, including merchant ships and fishing vessels, and promoting the upgrading of ship antifouling technology. Compared with existing technologies, this invention has the following beneficial effects:
[0029] The antifouling coating provided by this invention integrates the triple functions of "piezoelectric sterilization + traditional Chinese medicine slow release + super-slippery anti-adhesion", which significantly extends the antifouling cycle of ship hulls. The antifouling cycle of the coating can reach 5 to 8 years, far exceeding the traditional antifouling coating (1 to 3 years), reducing the frequency of ship coating replacement and lowering maintenance costs.
[0030] The antifouling coating provided by this invention uses berberine extract, a traditional Chinese medicine component, as a sustained-release agent. It is free of heavy metals and does not induce drug resistance. Furthermore, the leaching rate of the additives is controllable (0.1~0.5 mg / cm³). 2 •d), to avoid marine pollution caused by excessive release, fully complies with the International Convention for the Control of Hazardous Antifouling Systems, the Antifouling and Anti-rust Coating System for Ships (GB / T 6822-2024) and IMO environmental standards; excellent environmental performance.
[0031] The antifouling coating provided by this invention has an interfacial bonding strength of ≥15MPa for each layer, and its abrasion resistance (referring to GB / T31411-2015 "Determination of Abrasion Rate of Marine Antifouling Paint", dynamic simulation test of rotating drum, test plate linear speed (33.3±0.9)km / h, the abrasion rate meets the requirements of long-term antifouling paint after 5 consecutive cycles) is superior to existing low surface energy coatings; at the same time, the preparation process is compatible with existing marine coating production lines, has strong adaptability, and can be directly applied to different scenarios such as merchant ships, fishing vessels, and marine engineering equipment, with low industrialization difficulty.
[0032] The antifouling coating provided by this invention has outstanding static antifouling capability: the super-slippery biomimetic structure on the surface can form a dynamic water film, which can effectively prevent biological adhesion even in static environments such as ship berthing, solving the pain point of "static failure" of traditional physical antifouling coatings. The biological adhesion rate in static environments is ≤10% (refer to GB / T5370 "Antifouling Paint Sample Shallow Sea Immersion Test Method", the short-term antifouling paint is tested after immersion in one peak marine growth season, and the static adhesion rate of traditional coatings is ≥40%).
[0033] Furthermore, in this invention, the porous silica has a pore size of 50-200 nm and a porosity of 50-70%. By adjusting the pore size and porosity of the porous silica, this invention can precisely control the leaching rate of Coptis chinensis extract, ensuring that the slow-release period matches the antifouling period of the coating. Detailed Implementation
[0034] This invention provides an anti-fouling coating, comprising a bottom layer, an intermediate layer, and a top layer stacked sequentially;
[0035] The underlying slurry forming the bottom layer comprises the following components by mass fraction: 60-75% epoxy resin, 20-35% piezoelectric filler, 1-5% dispersant, and 0.5-3% defoamer;
[0036] The intermediate layer slurry forming the intermediate layer comprises the following components by mass fraction: 40-50% porous silica, 10-15% Coptis chinensis extract, 30-40% acrylic resin, and 3-5% organic toughening agent;
[0037] The surface slurry forming the surface layer comprises the following components by mass fraction: 80-90% polydimethylsiloxane, 5-10% earthworm mucus mimic, 3-8% crosslinking agent, and 0.5-3% catalyst, wherein the earthworm mucus mimic includes hyaluronic acid and glycerin.
[0038] In this invention, unless otherwise specified, all raw materials / components used in the preparation are commercially available products well known to those skilled in the art.
[0039] The antifouling coating provided by this invention includes a base layer. In this invention, the base layer slurry forming the base layer comprises the following components by mass fraction: 60-75% epoxy resin, 20-35% piezoelectric filler, 1-5% dispersant, and 0.5-3% defoamer. In embodiments of this invention, the mass fraction of the epoxy resin can be 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, or 75%. The piezoelectric filler preferably comprises zinc oxide whiskers and / or graphene, and in the embodiments, it can be zinc oxide whiskers. The zinc oxide whiskers are tetraneedle-shaped zinc oxide whiskers. The graphene is monolayer graphene and / or few-layer graphene. The diameter of the tetraneedle-shaped zinc oxide whiskers is preferably 0.5-2 μm, and the length is preferably 10-30 μm. The sheet thickness of the monolayer graphene and / or few-layer graphene is preferably 1-5 nm, and the lateral dimension is preferably 1-5 μm. In embodiments of the present invention, the mass fraction of the piezoelectric filler can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, or 30%. The dispersant is preferably BYK-163. In embodiments of the present invention, the mass fraction of the dispersant can be 1%, 1.5%, 2%, 2.5%, 3%, 4%, or 5%. The defoamer is preferably BYK-052. In embodiments of the present invention, the mass fraction of the defoamer can be 0.5%, 0.8%, 1%, 2%, or 3%.
[0040] The bactericidal efficiency of the substrate provided by this invention is as follows: ≥95% kill rate against Vibrio alginolyticus after 2 hours of treatment; ≥92% kill rate against barnacle larvae (Balanus amphitrite) after 4 hours of treatment.
[0041] The thickness of the substrate provided by this invention is preferably 50~80 μm. The dielectric constant (1kHz) of the substrate is ≥5, the piezoelectric constant d33 is ≥10 pC / N, and the adhesion (refer to GB / T 5210-2006 "Paints and Varnishes - Pull-off Adhesion Test", test column diameter 20 mm, single test column tested from one side) is ≥5 MPa, which meets the requirement of "Adhesion of anti-rust paint system without single-component products ≥5MPa" in GB / T 6822-2024.
[0042] The antifouling coating provided by this invention includes an intermediate layer stacked on the surface of a base layer. In this invention, the intermediate layer slurry forming the intermediate layer comprises the following components by mass fraction: 40-50% porous silica, 10-15% Coptis chinensis extract, 30-40% acrylic resin, and 3-5% organic toughening agent. In this invention, the porous silica preferably has a pore size of 50-200 nm and a porosity of 50-70%. In embodiments of this invention, the mass fraction of the porous silica can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, or 50%. In this invention, the Coptis chinensis extract preferably contains ≥90% berberine. The mass fraction of the Coptis chinensis extract can be 10%, 11%, 12%, 13%, 14%, or 15%. In embodiments of this invention, the mass fraction of the acrylic resin can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, or 40%. The organic toughening agent is preferably dibutyl phthalate. In embodiments of the present invention, the mass fraction of the organic toughening agent may be 3%, 3.5%, 4%, 4.5%, or 5%.
[0043] In this invention, the thickness of the intermediate layer is preferably 80-120 μm. The leaching rate of the intermediate layer is preferably 0.1-0.5 mg / cm³. 2 •d. Immersion resistance (refer to GB / T 10834-2008 "Determination of Salt Water Resistance of Marine Coatings - Salt Water and Hot Salt Water Immersion Method", the test solution is filtered natural seawater conforming to Class I in GB 3097-1997, the test temperature is (27±6)℃, after immersion for 140 days, the number of rust spots on the paint film does not exceed level 1, the size of rust spots does not exceed level S2, the bubble density does not exceed level 2, and the bubble size does not exceed level S3. After recoating, there is no blistering or peeling after immersion for another 35 days) meets the requirements of GB / T 6822-2024; under pH 7.5~8.5 and salinity 30~35‰ environment, the slow release period matches the antifouling period of the coating (5~8 years), meeting the requirement of "long-term antifouling paint service life not less than 5 years" in GB / T 6822-2024.
[0044] The antifouling coating provided by this invention includes a surface layer stacked on the surface of an intermediate layer. In this invention, the surface slurry forming the surface layer comprises the following components by mass fraction: 80-90% polydimethylsiloxane, 5-10% earthworm slime mimic, 3-8% crosslinking agent, and 0.5-3% catalyst. The earthworm slime mimic includes hyaluronic acid and glycerin. In embodiments of this invention, the mass fraction of the polydimethylsiloxane can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, or 90%. In this invention, the mass ratio of hyaluronic acid to glycerin is preferably 1:2 to 2:1, and in embodiments it can be 0.5:1, 0.8:1, 1:1, 1.5:1, or 2:1. In embodiments of this invention, the mass fraction of the earthworm slime mimic can be 5%, 6%, 7%, 8%, 9%, or 10%. In this invention, the crosslinking agent is preferably tetraethyl orthosilicate. In embodiments of the present invention, the mass fraction of the crosslinking agent can be 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 7.5%, or 8%. In the present invention, the catalyst preferably comprises tetrabutyl titanate (TBT) or γ-aminopropyltriethoxysilane (KH-550), and in the embodiments, tetrabutyl titanate can be used. In embodiments of the present invention, the mass fraction of the catalyst can be 0.5%, 1%, 2%, 2.5%, or 3%. The catalyst used in the present invention is an environmentally friendly catalyst.
[0045] In this invention, the thickness of the surface layer is preferably 5~10 μm. The surface energy of the surface layer is preferably ≤25 mN / m, the dynamic water film retention time is ≥72 h (under static conditions), and the bio-adhesion is ≤5 N / m. In this invention, the anti-blistering property (referring to GB / T 10834-2008, first cycle immersion at (88±3)℃ for 14 days, second cycle immersion at (38±2)℃ for 14 days, at least 2 test panels with no blistering (blistering within 6 mm of the edge is negligible)) meets the requirements of GB / T 6822-2024; the cathodic disbondment resistance (referring to Method B of GB / T 7790-2008 "Determination of Cathodic Disbondment Resistance of Coatings Exposed to Seawater", artificial pore diameter 6 mm, test time 182 days, average peel width ≤8.0 mm) meets the requirements of GB / T6822-2024.
[0046] This invention provides a method for preparing the antifouling coating described above, comprising the following steps:
[0047] Epoxy resin, piezoelectric filler, dispersant and defoamer are mixed to obtain a base slurry; the base slurry is coated on the substrate surface and then thermo-cured to obtain the base layer;
[0048] Coptis chinensis extract, alcohol solvent, and porous silica are mixed and loaded to obtain a supported carrier; the supported carrier, acrylic resin, and organic toughening agent are mixed to obtain an intermediate layer slurry; the intermediate layer slurry is coated on the surface of the bottom layer and then thermosetting to obtain an intermediate layer on the surface of the bottom layer.
[0049] Polydimethylsiloxane, earthworm slime mimic, crosslinking agent and catalyst are mixed to obtain a surface slurry; the surface slurry is coated on the surface of the intermediate layer and then thermo-cured to obtain a surface layer on the surface of the intermediate layer, thus obtaining the anti-fouling coating.
[0050] This invention involves mixing epoxy resin, piezoelectric filler, dispersant, and defoamer (hereinafter referred to as the first mixture) to obtain a base slurry; coating the base slurry (hereinafter referred to as the first coating) onto a substrate surface, and then subjecting it to thermosetting (hereinafter referred to as the first thermosetting) to obtain the base layer. In this invention, the first mixture is preferably carried out in a high-speed disperser. The first mixture is carried out under stirring conditions, with the stirring speed preferably being 1500~2000 r / min. The first mixing temperature is preferably 25~30℃. The first mixing time is preferably 30~45 min.
[0051] In this invention, the substrate is preferably a ship hull. The surface roughness of the substrate is preferably 5-10 μm. Before performing the first coating, the surface of the substrate is preferably pretreated. The pretreatment preferably includes sequential sandblasting and phosphating. This invention does not have specific requirements for the specific implementation of the sandblasting and phosphating treatments.
[0052] In this invention, the first coating is preferably applied by spraying. The spraying conditions preferably include: a spraying pressure of 0.3~0.5 MPa and a spraying distance of 20~30 cm. The first thermosetting is preferably carried out in an oven. The first thermosetting temperature is preferably 100~120℃; the curing time is preferably 2~3 h, forming the underlayer.
[0053] After obtaining the bottom layer, the present invention mixes Coptis chinensis extract, alcohol solvent and porous silica for loading to obtain a supported carrier; mixes the supported carrier, acrylic resin and organic toughening agent (hereinafter referred to as the second mixture) to obtain an intermediate layer slurry; coats the intermediate layer slurry (hereinafter referred to as the second coating) on the surface of the bottom layer, and then performs thermosetting (hereinafter referred to as the second thermosetting) to obtain an intermediate layer on the surface of the bottom layer.
[0054] In this invention, the method for preparing porous silica includes the following steps: mixing a surfactant, potassium chloride, and water to obtain a surfactant solution; mixing the surfactant solution, an inorganic acid solution, and a silicon source to obtain a sol solution; aging and drying the sol solution sequentially to obtain a dry gel; and calcining the dry gel to obtain the porous silica. In this invention, the surfactant is preferably hexadecyltrimethylammonium bromide. The water is preferably deionized water. The inorganic acid is preferably hydrochloric acid. The silicon source is preferably tetraethyl orthosilicate. The mixing temperature of the surfactant solution, inorganic acid solution, and silicon source is preferably room temperature, and the mixing time is preferably 2-3 hours, preferably under stirring conditions. The aging temperature is preferably room temperature, and the aging time is preferably 12-24 hours. The drying is preferably carried out in an oven, and the drying temperature is preferably 70-80°C, and the drying time is preferably 6-8 hours. The calcination is preferably carried out in a muffle furnace. The calcination temperature is preferably 500-550°C. The calcination holding time is preferably 6-8 hours. The preferred heating rate from room temperature to the calcination temperature is 5-10 °C / min. The calcination process is preferably used to remove the template agent (potassium chloride). After calcination, the material obtained is preferably cooled to room temperature and then ground to obtain the porous silica powder. The specific implementation method of the grinding process is not particularly important in this invention.
[0055] In this invention, the preferred method for preparing the Coptis chinensis extract includes the following steps: extracting Coptis chinensis with an ethanol-water solution to obtain an extract solution; concentrating the extract solution to obtain a paste; dissolving the paste in an acid solution and purifying it with a macroporous adsorption resin to obtain an eluent; and sequentially concentrating, crystallizing, and drying the eluent to obtain the Coptis chinensis extract. In this invention, prior to extraction, the Coptis chinensis is preferably pulverized and sieved sequentially. The mesh size of the Coptis chinensis is preferably 40 mesh. The volume fraction of ethanol in the ethanol-water solution is preferably 40-50%. The extraction is preferably performed multiple times, with the ratio of ethanol-water solution to Coptis chinensis used in each extraction preferably being 9 mL:1 g. The number of extractions is preferably 2-3 times. The extraction is preferably performed under reflux conditions, with the extraction temperature preferably being 60-65°C. The extraction time for each extraction is preferably 1-1.5 h. This invention preferably combines the filtrates obtained from multiple extractions to obtain the extract solution. The concentration is preferably performed under reduced pressure. The pH value of the acid solution used to dissolve the extract is preferably 1-1.5. Specifically, the acid solution can be a hydrochloric acid solution. After dissolution, the present invention preferably removes insoluble matter by filtration. The macroporous adsorption resin is preferably a D101 type macroporous adsorption resin. The purification preferably includes: pre-eluting with water as the eluent until the effluent is colorless; then eluting with an aqueous ethanol solution as the eluent, and collecting the eluent containing the aqueous ethanol solution. The volume fraction of ethanol in the aqueous ethanol solution is preferably 60%. The specific implementation method for concentrating the eluent is preferably vacuum concentration. The grain boundary is preferably carried out at room temperature. The present invention does not have special requirements for the specific implementation method of drying.
[0056] In this invention, the alcohol solvent is preferably ethanol. The preferred order of mixing the Coptis chinensis extract, alcohol solvent, and porous silica is as follows: dissolving the Coptis chinensis extract in the alcohol solvent to obtain an alcohol solution of the Coptis chinensis extract; then adding the porous silica to the alcohol solution of the Coptis chinensis extract and stirring. The mass content of the Coptis chinensis extract in the alcohol solution of the Coptis chinensis extract is preferably 5-10%. The stirring speed (i.e., the operating conditions for loading) is preferably 500-800 r / min, and the stirring time is preferably 2-3 h. By controlling the stirring conditions (i.e., the operating conditions for loading), this invention ensures that the Coptis chinensis extract is fully adsorbed into the pores of the porous silica support. After the loading is completed, this invention preferably dries the material obtained from the loading to obtain the powder of the loaded support. The drying is preferably vacuum drying. The vacuum drying temperature is preferably 50-60℃, and the time is preferably 4-6 h.
[0057] After obtaining the supported carrier, the present invention mixes the supported carrier, acrylic resin, and organic toughening agent (hereinafter referred to as the second mixture) to obtain an intermediate layer slurry; the intermediate layer slurry is coated (hereinafter referred to as the second coating) onto the surface of the bottom layer, and then thermosetting (hereinafter referred to as the second thermosetting) is performed to obtain the intermediate layer on the surface of the bottom layer. In the present invention, the second mixture is preferably carried out in a high-speed disperser. The second mixture is carried out under stirring conditions, and the stirring speed is preferably 1500~2000 r / min. The second mixing temperature is preferably 25~30℃. The second mixing time is preferably 20~30 min.
[0058] In this invention, the second coating is preferably applied by a blade. The thickness of the blade coating is preferably 80-120 μm. The second thermosetting is preferably carried out in an oven. The temperature of the second thermosetting is preferably 80-85°C; the curing time is preferably 1.5-2 h, forming an intermediate layer.
[0059] After obtaining the intermediate layer, the present invention mixes polydimethylsiloxane, earthworm slime mimic, crosslinking agent, and catalyst (hereinafter referred to as the third mixture) to obtain a surface slurry; the surface slurry is coated (hereinafter referred to as the third coating) onto the surface of the intermediate layer, and then thermosetting (hereinafter referred to as the third thermosetting) is performed to obtain a surface layer on the surface of the intermediate layer, thus obtaining the anti-fouling coating. In the present invention, during the third mixture, the polydimethylsiloxane preferably includes a PDMS main agent and a curing agent, and the mass ratio of the PDMS main agent to the curing agent is preferably 10:1. The third mixture is carried out under stirring conditions, and the stirring speed is preferably 800~1000 r / min. The third mixture temperature is preferably 25~30℃. The third mixture time is preferably 15~20 min. In the present invention, the surface slurry should be prepared and used immediately to avoid premature crosslinking.
[0060] In this invention, the third coating is preferably dip coating. The dip coating speed is preferably 5~10 cm / min. The dip coating thickness is preferably 5~10 μm. The third thermosetting is preferably carried out in an oven. The second thermosetting temperature is preferably 60~65℃; the curing time is preferably 0.5~1 h, forming a surface layer.
[0061] This invention provides the application of the antifouling coating described in the above technical solution or the antifouling coating prepared by the preparation method described in the above technical solution in ship antifouling.
[0062] To further illustrate the present invention, the technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0063] The methods for preparing porous silica used in the following examples and comparative examples specifically include:
[0064] Add 1.5 g of hexadecyltrimethylammonium bromide and 0.9 g of potassium chloride to 25 mL of deionized water and stir until completely dissolved to obtain a surfactant solution. Adjust the pH to 2 by adding 1 mol / L hydrochloric acid solution, and then add 4.2 g of tetraethyl orthosilicate (TEOS, density 0.93 g / cm³). 3 (Approximately 4.52 mL in volume) was stirred continuously at room temperature for 3 h to obtain a clear and transparent sol solution. After aging the sol solution for 12 h, it was transferred to an oven and dried at 80 °C for 6 h to obtain a dry gel. The dry gel was placed in a muffle furnace and heated to 550 °C at a heating rate of 5 °C / min for 6 h to remove the template agent. After cooling to room temperature, it was ground to obtain micro-nano porous silica powder with a pore size of 100 nm and a porosity of 60%.
[0065] The preparation methods of the Coptis chinensis extract used in the following examples and comparative examples specifically include:
[0066] Take 200g of dried Coptis chinensis herb, pulverize it and pass it through a 40-mesh sieve. Add 9 times the volume of 50% ethanol solution and reflux extract twice at 60℃ for 1 hour each time. Combine the two extracts and filter. Concentrate the filtrate under reduced pressure until there is no alcohol odor to obtain an extract. Dissolve the extract in hydrochloric acid solution at pH=1, filter to remove insoluble matter, and pass the filtrate through a D101 macroporous adsorption resin column. First, elute with water until the eluent is colorless, then elute with 60% ethanol solution and collect the ethanol eluent. Concentrate the eluent under reduced pressure and crystallize at room temperature. Filter to obtain crystals, and dry to obtain Coptis chinensis extract containing 92wt% berberine. HPLC was used to detect the berberine content in the Coptis chinensis extract. The extract of Coptis chinensis does not contain heavy metals, organotin (referring to GB / T26085 "Test and Judgment of Total Tin Content in Marine Antifouling Paint", total tin ≤2500 mg / kg), DDT (referring to GB / T25011 "Test and Judgment of DDT Content in Marine Antifouling Paint", DDT content ≤1000 mg / kg), or sibutrali (referring to Appendix C of GB / T6822-2024 "Determination of Sibutrali Content in Antifouling Paint", sibutrali content ≤200 mg / kg), and meets the limit requirements for biocidal agent content in GB / T6822-2024.
[0067] The ship steel plates used in the following examples and comparative examples require pretreatment. The specific pretreatment methods include: sandblasting and rust removal followed by phosphating treatment on the ship steel plates in sequence. The roughness Ra of the pretreated ship steel plates is 5~10μm.
[0068] Example 1
[0069] Substrate preparation: 68% epoxy resin, 25% zinc oxide whiskers, 4% BYK-163, and 3% BYK-052 were added to a high-speed disperser and dispersed at 2000 r / min for 40 min at 25-30℃ to form a uniform substrate slurry. The substrate slurry was then sprayed onto the pretreated ship steel plate surface at a pressure of 0.4 MPa and a distance of 30 cm. It was then cured at 120℃ for 2 h to form the substrate. The substrate thickness was 65 μm, with a dielectric constant of 6, a piezoelectric constant d33 of 12 pC / N, and an adhesion of 6 MPa.
[0070] Intermediate layer preparation: 12% of Coptis chinensis extract (containing 92% berberine) was dissolved in ethanol to form an ethanol solution of Coptis chinensis extract, wherein the content of Coptis chinensis extract in the ethanol solution was 5 wt%. 45% porous silica (pore size 100 nm, porosity 60%) was added to the ethanol solution of Coptis chinensis extract and stirred for 3 h at 30-40℃ and 800 r / min to allow the Coptis chinensis extract to be fully adsorbed into the pores of the porous silica. Then, it was dried in a vacuum drying oven at 60℃ for 6 h to obtain the supported carrier. The supported carrier, 38% acrylic resin, and 5% dibutyl phthalate were added to a disperser and dispersed for 30 min at 1500 r / min and 25-30℃ to form an intermediate layer slurry. The intermediate layer slurry was coated onto the surface of the bottom layer by a blade coating method, with the coating thickness controlled at 100 μm. Then, it was cured in an oven at 80℃ for 1.5 h to form the intermediate layer. The leaching rate of the intermediate layer was 0.3 mg / cm³. 2 ·d.
[0071] Surface preparation: 85% PDMS (PDMS main agent and curing agent, mass ratio of 10:1), 8% earthworm mucus mimic (hyaluronic acid: glycerol = 1:1, mass ratio), 4% tetraethyl orthosilicate, and 3% tetrabutyl titanate were stirred at 1000 r / min for 20 min at 25~30℃ to obtain a surface slurry (it should be prepared and used immediately to avoid premature cross-linking). The surface slurry was coated onto the surface of the intermediate layer by dip coating at a speed of 8 cm / min. It was then cured in a 60℃ oven for 1 h and cooled to room temperature to obtain a surface layer with a thickness of 8 μm, a surface energy of 22 mN / m, and a dynamic water film retention time of 80 h, thus obtaining an antifouling coating.
[0072] Performance test results of the antifouling coating prepared in Example 1: antifouling period of 7 years, static bio-adhesion rate of 8%, interfacial bonding strength of 18 MPa, and weight loss of 4 mg in Taber abrasion test.
[0073] Antifouling period: 7 years (referring to GB / T7789 "Dynamic Test Method for Antifouling Performance of Marine Antifouling Paint", according to the test procedure of Type III antifouling paint, 3 cycles for short-term effect, 5 cycles for medium-term effect, and 8 cycles for long-term effect, with the last cycle in the peak season of marine organism growth, combined with the immersion test results of 3 peak seasons of marine organism growth in shallow sea (GB / T5370) to estimate), which meets the requirements of long-term antifouling paint (GB / T6822-2024).
[0074] Static biofilm adhesion rate: 8% (referring to GB / T5370, using a Type III antifouling and anti-rust paint system, and immersing in shallow sea for one peak marine growth season; the 20 mm edge of the test plate is not included in the evaluation area).
[0075] Interface bonding strength: 18 MPa (refer to GB / T5210-2006, test column diameter 20 mm, single test column, single side test), which is better than the requirement of "adhesion of anti-rust paint system without single component products ≥5 MPa" in GB / T6822-2024.
[0076] Abrasion rate: Referring to GB / T31411-2015 "Determination of Abrasion Rate of Marine Antifouling Paint", a rotating drum dynamic simulation test device was used. The linear speed of the test plate was (33.3±0.9) km / h. After the drum ran continuously for 9 days, it was immersed in seawater for 21 days as one cycle. After 5 consecutive cycles, the abrasion rate met the requirements of long-term effective Type I antifouling paint.
[0077] Biocidal agent content: Total copper (GB / T31409 Determination of Total Copper Content in Marine Antifouling Paints) was not detected. The content of copper-free biocidal agents (berberine) met the agreed value. The contents of organotin, DDT, and sibuprofen all met the requirements of GB / T6822-2024.
[0078] Example 2
[0079] Underlayer preparation: 62% epoxy resin, 30% zinc oxide whiskers, 5% BYK-163, and 3% BYK-052 were added to a high-speed disperser and dispersed at 1800 r / min for 45 min at 25-30℃ to form a uniform underlayer slurry. The underlayer slurry was then sprayed onto the pretreated ship steel plate surface at a spray pressure of 0.5 MPa and a spray distance of 30 cm. It was then cured at 120℃ for 2 h to form the underlayer. The underlayer thickness was 80 μm, with a dielectric constant of 7, a piezoelectric constant d33 of 15 pC / N, and an adhesion of 7 MPa.
[0080] Intermediate layer preparation: 15% of Coptis chinensis extract (containing 92% berberine) was dissolved in ethanol to form an ethanol solution of Coptis chinensis extract, wherein the content of Coptis chinensis extract in the ethanol solution was 5 wt%. 50% porous silica (pore size 100 nm, porosity 60%) was added to the ethanol solution of Coptis chinensis extract and stirred for 3 h at 30-40℃ and 800 r / min to allow the Coptis chinensis extract to be fully adsorbed into the pores of the porous silica. Then, it was dried in a vacuum drying oven at 60℃ for 6 h to obtain the supported carrier. The supported carrier, 30% acrylic resin, and 5% dibutyl phthalate were added to a disperser and dispersed for 30 min at 1500 r / min and 25-30℃ to form an intermediate layer slurry. The intermediate layer slurry was coated onto the surface of the bottom layer by a blade coating method, with the coating thickness controlled at 120 μm. Then, it was cured in an oven at 80℃ for 1.5 h to form the intermediate layer. The leaching rate of the intermediate layer was 0.5 mg / cm. 2 ·d.
[0081] Surface preparation: 89% PDMS (PDMS main agent and curing agent, mass ratio 10:1), 5% earthworm mucus mimic (hyaluronic acid: glycerol = 1:2, mass ratio), 4% tetraethyl orthosilicate, and 2% tetrabutyl titanate were stirred at 900 r / min for 18 min at 25-30℃ to obtain a surface slurry (it should be prepared and used immediately to avoid premature cross-linking). The surface slurry was coated onto the surface of the intermediate layer using a dip-coating method at a dip-coating speed of 10 cm / min, and then cured in a 60℃ oven for 1 h. After cooling to room temperature, a surface layer with a thickness of 10 μm, a surface energy of 20 mN / m, and a dynamic water film retention time of 90 h was obtained, resulting in an antifouling coating.
[0082] Performance test results of the antifouling coating prepared in Example 2: antifouling period of 8 years, static bio-adhesion rate of 6%, interfacial bonding strength of 20 MPa, and weight loss of 3 mg in Taber abrasion test.
[0083] Antifouling period: 8 years (based on GB / T7789 and calculated using GB / T53703 results of immersion during the peak growth season of marine organisms), meeting the requirements for long-term antifouling paint (GB / T6822-2024).
[0084] Static biofilm attachment rate: 6% (refer to GB / T5370, shallow sea immersion during one peak marine growth season).
[0085] Interface bonding strength: 20 MPa (refer to GB / T5210-2006).
[0086] Abrasion rate: According to GB / T31411-2015, it meets the requirements of long-term effective Type I antifouling paint after 5 consecutive cycles.
[0087] Biocidal agent content: Total copper was not detected, berberine content met the agreed value, and organotin, DDT, and sibuprofen content met the requirements of GB / T6822-2024.
[0088] Example 3
[0089] Substrate preparation: 72% epoxy resin, 20% zinc oxide whiskers, 5% BYK-163, and 3% BYK-052 were added to a high-speed disperser and dispersed at 1500 r / min for 30 min at 25-30℃ to form a uniform substrate slurry. The substrate slurry was then sprayed onto the pretreated ship steel plate surface at a spray pressure of 0.3 MPa and a spray distance of 30 cm. It was then cured at 120℃ for 2 h to form the substrate. The substrate thickness was 50 μm, with a dielectric constant of 5, a piezoelectric constant d33 of 10 pC / N, and an adhesion of 5 MPa.
[0090] Intermediate layer preparation: 10% of Coptis chinensis extract (containing 92% berberine) was dissolved in ethanol to form an ethanol solution of Coptis chinensis extract, wherein the content of Coptis chinensis extract in the ethanol solution was 5 wt%. 42% porous silica (pore size 100 nm, porosity 60%) was added to the ethanol solution of Coptis chinensis extract and stirred for 3 h at 30-40℃ and 800 r / min to allow the Coptis chinensis extract to be fully adsorbed into the pores of the porous silica. Then, it was dried in a vacuum drying oven at 60℃ for 6 h to obtain the supported carrier. The supported carrier, 45% acrylic resin, and 3% dibutyl phthalate were added to a disperser and dispersed for 30 min at 1500 r / min and 25-30℃ to form an intermediate layer slurry. The intermediate layer slurry was coated onto the surface of the bottom layer by a blade coating method, with the coating thickness controlled at 80 μm. Then, it was cured in an oven at 80℃ for 1.5 h to form the intermediate layer. The leaching rate of the intermediate layer was 0.1 mg / cm²·d.
[0091] Surface preparation: 80% PDMS (PDMS main agent and curing agent, mass ratio 10:1), 10% earthworm mucus mimic (hyaluronic acid: glycerol = 2:1, mass ratio), 7.5% tetraethyl orthosilicate, and 2.5% tetrabutyl titanate were stirred at 800 r / min for 15 min at 25-30℃ to obtain a surface slurry (it should be prepared and used immediately to avoid premature cross-linking). The surface slurry was coated onto the surface of the intermediate layer using a dip-coating method at a dip-coating speed of 5 cm / min, and then cured in a 60℃ oven for 1 h. After cooling to room temperature, a surface layer with a thickness of 5 μm, a surface energy of 25 mN / m, and a dynamic water film retention time of 72 h was obtained, resulting in an antifouling coating.
[0092] Performance test results of the antifouling coating prepared in Example 3: antifouling period of 5 years, static bio-adhesion rate of 10%, interfacial bonding strength of 15 MPa, and Taber abrasion test weight loss of 5 mg.
[0093] Antifouling period: 5 years (based on GB / T7789 and calculated using GB / T53703 results of immersion during the peak marine growth season), meeting the requirements for long-lasting antifouling paint (GB / T6822-2024).
[0094] Static biofilm attachment rate: 10% (refer to GB / T5370, shallow sea immersion during one peak marine growth season).
[0095] Interface bonding strength: 15 MPa (refer to GB / T5210-2006), meeting the requirements of GB / T6822-2024.
[0096] Abrasion rate: According to GB / T31411-2015, it meets the requirements of long-term effective Type I antifouling paint after 5 consecutive cycles.
[0097] Biocidal agent content: Total copper was not detected, berberine content met the agreed value, and organotin, DDT, and sibuprofen content met the requirements of GB / T6822-2024.
[0098] Comparative Example 1 (Conventional Single-Function Coating: Super-Slippery Layer Only)
[0099] Coating composition: 95% PDMS, 4% crosslinking agent, 1% catalyst, prepared by the same method as the surface layer in Example 1 of this invention.
[0100] Performance testing: Antifouling period: 2 years (refer to GB / T7789, according to the Type V antifouling paint test procedure, calculated after one season of shallow sea immersion during the peak marine growth season), only meets the requirements for short-term antifouling paint (GB / T6822-2024).
[0101] Static bio-attachment rate: 45% (refer to GB / T5370, shallow sea immersion during one peak marine growth season), far exceeding the coating of this invention.
[0102] Interface bonding strength: 8 MPa (refer to GB / T5210-2006), lower than the coating of this invention.
[0103] Abrasion rate: According to GB / T31411-2015, the abrasion rate after 5 consecutive cycles does not meet the requirements of long-term antifouling paint.
[0104] Foaming resistance: Referring to GB / T10834-2008, a small amount of foaming occurred in the second cycle, which does not meet the requirements of GB / T6822-2024; this proves that a single super-slippery layer cannot achieve long-term antifouling and has poor mechanical properties and foaming resistance.
[0105] Comparative Example 2 (Conventional Composite Coating: No Piezoelectric Layer)
[0106] Coating composition: intermediate layer (same as Example 1) + top layer (same as Example 1), no underlayer.
[0107] Performance testing: Antifouling period: 3.5 years (referring to GB / T7789, calculated after one season of shallow sea immersion during the peak marine growth season according to the Type V antifouling paint test procedure), which only meets the requirements of medium-term antifouling paint (GB / T6822-2024), shorter than the coating of this invention.
[0108] Static bio-attachment rate: 25% (refer to GB / T5370, shallow sea immersion during one peak marine growth season), higher than the coating of this invention.
[0109] Interfacial bonding strength: 10 MPa (refer to GB / T5210-2006), lower than the coating of this invention.
[0110] Cathodic disbondment resistance: According to GB / T7790-2008, the average disbondment width is 9.5 mm, which does not meet the requirement of "≤8.0 mm" in GB / T6822-2024; this proves that without the piezoelectric layer, the physical sterilization function is lost, the antifouling cycle is significantly shortened, the static antifouling ability is reduced, and the cathodic disbondment resistance does not meet the standard.
[0111] Comparative Example 3 (Traditional Chinese Medicine Coating: No Super-Slippery Layer)
[0112] Coating composition: base layer (same as Example 1) + intermediate layer (same as Example 1), no top layer.
[0113] Performance testing: Antifouling period: 4 years (referring to GB / T7789, calculated after one season of shallow sea immersion during the peak marine growth season according to the Type V antifouling paint test procedure), which only meets the requirements of medium-term antifouling paint (GB / T6822-2024), shorter than the coating of this invention.
[0114] Static bio-attachment rate: 30% (refer to GB / T5370, shallow sea immersion during one peak marine growth season), higher than the coating of this invention.
[0115] Surface energy: 45 mN / m, which is much higher than the surface layer of this invention.
[0116] Anti-foaming property: According to GB / T10834-2008, obvious foaming occurred in the second cycle, which does not meet the requirements of GB / T6822-2024; this proves that without the super-slippery layer, biological organisms are easy to adhere in a static environment, the antifouling period cannot reach more than 5 years, and the anti-foaming property does not meet the standard.
[0117] Comparative Example 4
[0118] The preparation method is basically the same as in Example 1, except that chitosan is used instead of porous silica as the slow-release carrier. Although chitosan is environmentally friendly, it is easily degraded in high-salt marine environments. The slow-release period of the antifouling coating prepared in this comparative example is only 2-3 years, which cannot meet the antifouling requirements of more than 5 years.
[0119] Comparative Example 5
[0120] The preparation method is basically the same as that in Example 1, except that fluorocarbon resin is used to replace PDMS in the surface layer of Example 1 as the super-slippery layer matrix. Fluorocarbon resin has a lower surface energy, but the preparation method of the surface layer is complicated (requiring high-temperature curing ≥150℃), which is not compatible with existing marine coating production lines (conventional curing temperature ≤120℃).
[0121] As can be seen from the above embodiments, the antifouling coating provided by the present invention has an extended antifouling cycle and static antifouling capability. The antifouling coating provided by the present invention adopts the functional synergy of "bottom piezoelectric layer (physical sterilization) + middle slow-release layer (chemical antibacterial) + surface super-slippery layer (physical anti-adhesion)", as well as the design of the porosity regulation of the middle slow-release layer and the dynamic water film of the surface super-slippery layer. All performance indicators meet the requirements of GB / T 6822-2024 for long-term antifouling paint systems.
[0122] Meanwhile, the antifouling coating provided by this invention has environmental protection properties. This invention uses Coptis chinensis extract as a traditional Chinese medicine sustained-release agent in the intermediate layer. It is free of heavy metals, organotin compounds, DDT, and sibuprofen, and meets the requirements for the content of biocides in GB / T 6822-2024.
[0123] The anti-fouling coating provided by this invention has good mechanical properties and compatibility. The preparation method of this invention is "layer-by-layer coating-gradient curing", and the raw materials of each layer (epoxy resin, PDMS, etc.) are compatible with existing coating systems. Moreover, the adhesion, abrasion resistance and other indicators meet the requirements of GB / T 6822-2024 for the performance of coating systems.
[0124] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An anti-fouling coating, characterized in that, The bottom layer, the intermediate layer and the surface layer are sequentially stacked; The bottom layer slurry for forming the bottom layer comprises the following components in mass fraction: epoxy resin 60-75%, piezoelectric filler 20-35%, dispersing agent 1-5%, defoaming agent 0.5-3%; The intermediate layer slurry for forming the intermediate layer comprises the following components in mass fraction: porous silica 40-50%, Coptis extract 10-15%, acrylic resin 30-40%, organic toughening agent 3-5%; The surface layer slurry for forming the surface layer comprises the following components in mass fraction: polydimethylsiloxane 80-90%, earthworm mucus simulator 5-10%, crosslinking agent 3-8%, catalyst 0.5-3%, the earthworm mucus simulator comprising hyaluronic acid and glycerol; The preparation method of the anti-fouling coating comprises the following steps: The epoxy resin, the piezoelectric filler, the dispersing agent and the defoaming agent are mixed to obtain the bottom layer slurry; the bottom layer slurry is coated on the surface of the substrate, and then heat curing is performed to obtain the bottom layer; The Coptis extract, the alcohol solvent and the porous silica are mixed to obtain a supported carrier; the supported carrier, the acrylic resin and the organic toughening agent are mixed to obtain the intermediate layer slurry; the intermediate layer slurry is coated on the surface of the bottom layer, and then heat curing is performed to obtain the intermediate layer on the surface of the bottom layer; The polydimethylsiloxane, the earthworm mucus simulator, the crosslinking agent and the catalyst are mixed to obtain the surface layer slurry; the surface layer slurry is coated on the surface of the intermediate layer, and then heat curing is performed to obtain the surface layer on the surface of the intermediate layer, thereby obtaining the anti-fouling coating.
2. The anti-fouling coating according to claim 1, characterized in that, The piezoelectric filler comprises zinc oxide whiskers and / or graphene; the dispersing agent is BYK-163, and the defoaming agent is BYK-052.
3. The anti-fouling coating according to claim 1, wherein The porous silica has a pore size of 50-200 nm and a porosity of 50-70%; the Coptis extract contains berberine ≥ 90wt%; the organic toughening agent is dibutyl phthalate.
4. The stain resistant coating of claim 1, wherein, The mass ratio of the hyaluronic acid to the glycerol is 1:2-2:1; the crosslinking agent is tetraethyl orthosilicate; and the catalyst comprises tetrabutyl titanate or γ-aminopropyl triethoxysilane.
5. The stain resistant coating of any one of claims 1-4, wherein, The thickness of the bottom layer is 50-80 μm; the thickness of the intermediate layer is 80-120 μm; and the thickness of the surface layer is 5-10 μm.
6. The method of producing the anti-fouling coating according to any one of claims 1 to 5, characterized in that, The preparation method of the anti-fouling coating comprises the following steps: The epoxy resin, the piezoelectric filler, the dispersing agent and the defoaming agent are mixed to obtain the bottom layer slurry; the bottom layer slurry is coated on the surface of the substrate, and then heat curing is performed to obtain the bottom layer; The Coptis extract, the alcohol solvent and the porous silica are mixed to obtain a supported carrier; the supported carrier, the acrylic resin and the organic toughening agent are mixed to obtain the intermediate layer slurry; the intermediate layer slurry is coated on the surface of the bottom layer, and then heat curing is performed to obtain the intermediate layer on the surface of the bottom layer; The polydimethylsiloxane, the earthworm mucus simulator, the crosslinking agent and the catalyst are mixed to obtain the surface layer slurry; the surface layer slurry is coated on the surface of the intermediate layer, and then heat curing is performed to obtain the surface layer on the surface of the intermediate layer, thereby obtaining the anti-fouling coating.
7. The preparation method according to claim 6, characterized in that, The preparation method of the porous silica comprises the following steps: Mixing a surfactant, potassium chloride and water to obtain a surfactant solution; Mixing the surfactant solution, an inorganic acid solution and a silicon source to obtain a sol solution; Aging and drying the sol solution in sequence to obtain a dry gel; Calcining the dry gel to obtain the porous silicon dioxide.
8. The preparation method according to claim 6, characterized in that, The preparation method of the Coptis extract comprises the following steps: Extracting Coptis medicinal materials with an ethanol aqueous solution to obtain an extraction solution; concentrating the extraction solution to obtain an extract; dissolving the extract with an acid solution and then purifying it with a macroporous adsorption resin to obtain an eluate; and sequentially concentrating, crystallizing and drying the eluate to obtain the Coptis extract.
9. The preparation method according to claim 6, characterized in that, The base is a ship shell; and the surface roughness of the base is 5-10 μm.
10. Use of the antifouling coating according to any one of claims 1-5 or the antifouling coating prepared by the preparation method according to any one of claims 6-9 in ship antifouling.
Citation Information
Patent Citations
Polymeric binder and high molecular weight polymer antifouling compositions
EP4106817A1
Antifouling coating composition
JP2000129170A